Constructions of Deafness: Exploring Normalcy and Deviance within Specific Social Representations - Horejes, Thomas P. (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2009)
The constructions of deafness and social representations of a deaf child are very complicated and deeply contested. This paper examines the constructions of deafness and how it has been sociohistorically framed and re-framed within the parameters of normalcy and deviance. Such analysis may offer insight on the potential impact of shaping ideology, politics, and what it means to be deaf. This level of analysis is conducted via an examination of the socio-history of deaf education including discussions of the ongoing “paradigm wars” between certain social control institutions, mainly American Sign Language-based (or called English-based) and the oral-based educational institutions and its implications of language. Examining these two social control institutions will seek to uncover certain constructions within specific social representations and societal dynamics that may shape the deaf child’s identity, its version of “natural” gifts, social inequality, and ultimately the types of ideologies constructed toward deaf students. A possible alternative view of reapproprating of the corporeal differences of deafness is discussed including positive strategies to minimize reproduced social stratification, oppression, social inequality, and divisions when dealing with deafness.